2011
DOI: 10.3233/bmr-2011-0289
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of diadynamic currents and transcutaneous electrical nerve stimulation in disc disease lumbar part of spine

Abstract: DD current and TENS therapies in low back discopathy have an analgesic impact and improve functional fitness. The applied therapies have a comparable impact on researched parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 6 publications
1
25
1
1
Order By: Relevance
“…A study conducted by Ratajczak B, Hawrylak A et al to compare the efficiency of analgesic Diadynamic current therapy and TENS in low back discopathy in age group of 45 to 60 years who was diagnosed with low back pain syndrome due to discopathy where subjected to therapy. On the basis of research they concluded that Diadynamic current and TENS therapies in low back discopathy have an analgesic impact and improve functional fitness [7]. Present study agreed with a clinical trial by Philipson T, et al on the application of Diadynamic current on chronic soft-tissue pain in the neck and shoulder girdle.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A study conducted by Ratajczak B, Hawrylak A et al to compare the efficiency of analgesic Diadynamic current therapy and TENS in low back discopathy in age group of 45 to 60 years who was diagnosed with low back pain syndrome due to discopathy where subjected to therapy. On the basis of research they concluded that Diadynamic current and TENS therapies in low back discopathy have an analgesic impact and improve functional fitness [7]. Present study agreed with a clinical trial by Philipson T, et al on the application of Diadynamic current on chronic soft-tissue pain in the neck and shoulder girdle.…”
Section: Discussionsupporting
confidence: 86%
“…There were 80 sample size in which group A of 40 individuals were given Diadynamic current therapy and group B of 40 individuals were given TENS therapy. On the basis of research they concluded that Diadynamic current and TENS therapies in low back discopathy have an analgesic impact and improve functional fitness [7].…”
mentioning
confidence: 99%
“…Ratajczak B et al (2011) showed that diadynamic currents (DDC) and transcutaneous electrical nerve stimulation (TENS) have analgesic effect in treating sciatic syndrome (lat. ischialgia) [24]. However, electrical stimulation shows several crucial drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Faradic and diadynamic stimulations promoted the most significant enhancement in both speed and cathodal directionality amongst the physical therapy waveforms. Faradic stimulation is known to promote collagen organization whereas diadynamic stimulation is one of the mostly used electrotherapeutic methods for soft tissue injury 16, 29. It is interesting to note that while HVPGS has been demonstrated to increase proliferation, collagen synthesis and skin wound healing, no significant effect of increased cell migration was found 30.…”
Section: Discussionmentioning
confidence: 99%